Addressing MSMEs Customer Complaints in Indonesia’s Digital Economy: Insights from Sharia and Consumer Protection Law - Astuti, Miguna; Mardiatmi, Anastasia Bernadin Dwi; Sari, Afrina; Dewi, Fransisca Iriani Roesmala (JURIS (Jurnal Ilmiah Syariah), 2024)
This study examines MSME customer segmentation based on complaint behavior and the influence of Recency, Frequency, and Monetary (RFM) metrics. It integrates consumer protection law in Indonesia and sharia principles to address customer complaints. Using a mixed-method approach, quantitative analysis of RFM data and descriptive segmentation were combined with qualitative normative legal analysis. Data collection involved online and offline surveys in the Jabodetabek area using structured questionnaires covering RFM metrics, demographics, and complaint patterns. Findings reveal that 35.57% of MSMEs 4.0 customers belong to the "Faithful Customers" segment, characterized by loyalty despite limited financial contributions, crucial for business sustainability. Most customers, particularly younger and low-income groups, exhibit passive complaint behavior, favoring informal expressions of dissatisfaction over formal mechanisms. This highlights the need for strategies that prioritize emotional engagement and non-confrontational feedback to enhance retention and satisfaction. From the perspectives of Indonesian consumer protection law and sharia law, MSMEs must provide effective complaint channels and uphold fairness, transparency, and deliberation. These principles are vital for maintaining customer trust and ensuring long-term business success, emphasizing the importance of aligning customer engagement with ethical and legal standards.